KOMITE AUDIT SEBAGAI PEMODERASI PENGARUH KESULITAN KEUANGAN DAN MANAJEMEN LABA TERHADAP KECURANGAN LAPORAN KEUANGAN - Agustina Riyanti (Jurnal Akuntansi dan Pajak, 2024)
This study aims to examine financial distress and earnings management on financial statement fraud with audit committee as a moderating variable in the financial statement report of industrial companies listed on the Indonesia Stock Exchange in 2015-2021. Financial statement fraud is measured using the f-score model. The research sample was obtained by the purposive sampling technique. Research testing includes descriptive statistical tests, normality tests, coefficient of determination tests, panel data analysis, and influence testing using moderate regression (MRA). The research results show that financial distress have a positive effect on fraudulent financial statements and earnings management influences fraudulent financial statements. However, this research does not find that the audit committee can play a moderating role in the influence of financial difficulties and earnings management on financial statements